Gut microbiota, metabolites, and cytokines in relation to the risk of prostate cancer in the Asian population - Wang, Zhengshi; Chen, Haotian; Liu, Yongqiang; Zou, Libin; Zhang, Zhijin; Yin, Zhiqiang; Mao, Shiyu; Guo, Changcheng; Yang, Bin; Wu, Pengfei; Yao, Xudong (Frontiers in Oncology, 2025)
PurposeStudies have shown that gut microbiota is involved in the tumorigenesis and development of prostate cancer. We aimed to perform a comprehensive analysis of causal associations of gut microbiota, metabolites, and cytokines with prostate cancer in the Asian population.Patients and methodsGenome-wide association study (GWAS) summary datasets were collected from the public databases. There were 418 bacterial traits, 452 metabolites, 91 cytokines, 5408 cases of prostate cancer from East Asia, and 109,347 controls included. Mendelian randomization (MR) analyses were performed to investigate their causal relationships. Sensitivity analyses were conducted to test the reliability of MR results. Furthermore, the FinnGen database was used to assess the generalizability of our findings based on Asians.ResultsThere were a total of 17 bacterial traits, 28 metabolites (including 2 microbiota-associated metabolites), and 9 cytokines to be significantly associated with prostate cancer in Asians (P < 0.05). Further MR analyses of these positive results indicated that G_Ruminococcaceae UCG014/TNFSF10 axis, G_Anaerofilum/TNFRSF14 axis, G_Erysipelotrichaceae UCG003/TNFSF10 axis, and P_Proteobacteria/cholesterol axis were key signaling pathways involved in the progression of prostate cancer. Notably, G_Ruminococcaceae UCG014/TNFSF10 axis and G_Anaerofilum/TNFRSF14 axis were found to act as protective factors, while the other two signaling axes played a crucial role in promoting the progression of prostate cancer. Sensitivity analyses further confirmed the reliability of our findings. Using the European population as outcome, we further assessed the generalizability of our conclusions and found limited applicability to Europeans.ConclusionsWe found that there were causal associations of gut microbiota, metabolites, and cytokines with prostate cancer in Asians. The causal effects of gut microbiota on prostate cancer were partially mediated by metabolites and cytokines. These findings might contribute to the development of new therapeutic strategies for prostate cancer.